1999
DOI: 10.2527/1999.774988x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yeast culture (Saccharomyces cerevisiae) on adaptation of cows to postpartum diets and on lactational performance.

Abstract: Multiparous (n = 26) and primiparous (n = 18) Holstein cows were fed prepartum and postpartum total mixed diets that were, or were not, supplemented with a yeast culture (YC) for approximately 23 d prepartum and 56 d postpartum. Multiparous cows supplemented with YC selected a prepartum diet higher in CP than did unsupplemented cows, although prepartum performance of cows of both parities, as assessed by DMI and measures of body status, was not influenced by YC. The extent of the prepartum DMI depression was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
54
1
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 13 publications
(23 reference statements)
14
54
1
8
Order By: Relevance
“…Differences between the groups were not significant (P>0.05). The results in this trial confirm those of Williams et al, (1991), Wohlt et al, (1991Wohlt et al, ( , 1998, Robinson and Garrett (1999), and Dann et al, (2000), who observed that feed additives improvement in DM intake when lactating cows were fed. Supplementation with a blend of cinnamaldehyde and eugenol as a feed additive can increase DMI and milk production in lactating dairy cows (Wall 2014).…”
Section: Dry Matter Intake (Kg/day)supporting
confidence: 82%
“…Differences between the groups were not significant (P>0.05). The results in this trial confirm those of Williams et al, (1991), Wohlt et al, (1991Wohlt et al, ( , 1998, Robinson and Garrett (1999), and Dann et al, (2000), who observed that feed additives improvement in DM intake when lactating cows were fed. Supplementation with a blend of cinnamaldehyde and eugenol as a feed additive can increase DMI and milk production in lactating dairy cows (Wall 2014).…”
Section: Dry Matter Intake (Kg/day)supporting
confidence: 82%
“…Alguns autores observaram aumentos na ingestão de matéria seca (Williams et al, 1991;Wohlt et al, 1998), enquanto outros não observaram efeito algum (Piva et al, 1993;Robinson et al, 1999). Piva et al (1993) sugeriram que vários fatores afetam a resposta de vacas leiteiras à suplementação com levedura, destacando o estádio de lactação, o tipo de forragem fornecida, a estratégia de alimentação e a proporção volumoso:concentrado da dieta.…”
Section: Tabela 2 -Composição Das Dietas Experimentais (% Ms)unclassified
“…Apesar do interesse crescente pelo uso de probióticos para vacas leiteiras, os resultados de pesquisas com leveduras têm variado bastante. Aumentos na produção de leite em vacas leiteiras alimentadas com levedura têm sido observados por diversos pesquisadores (Williams et al, 1991;Piva et al, 1993;Adams et al, 1995;Putman et al, 1997;Kung et al, 1997;Robinson & Garret, 1999;Wohlt et al, 1998;Chaucheyras-Durand et al, 1998), mas, em alguns trabalhos, não foram relatados resultados positivos (Arambel & Kent, 1990;Dann et al, 2000;Soder & Holden, 1999;Swartz et al, 1994).…”
Section: Tabela 2 -Composição Das Dietas Experimentais (% Ms)unclassified
See 2 more Smart Citations